2002
DOI: 10.1351/pac200274112083
|View full text |Cite
|
Sign up to set email alerts
|

Thick films of ceramic superconducting, electro-ceramic materials

Abstract: The use of thick films becomes more and more important in particular for electronic and microelectronic applications. The term “thick film ” does not relate so much to the thickness of the film but more to the kind of deposition. Thick films are made by low-priced processes such as doctor (dr) blading, screen-printing, or spraying methods, etc. The preparation of thick films of ceramic material by these methods generally implies a processing sequence of the following steps: preparation of the oxide powders; pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…The starting ceramics were synthesized by sintering route (1040 o C, 4 h duration) using reagent grade Cu carbonate hydroxide, and Ni, Co, Mn carbonate hydroxide hydrates [12][13][14]. The paste was prepared by mixing powder of basic Cu 0.1 Ni 0.1 Co 1.6 Mn 1.2 O 4 ceramics with МБ-60 glass, Bi 2 O 3 (used as inorganic binder) and some organic vehicle.…”
Section: Nanoinhomogeneous Ceramics Preparationmentioning
confidence: 99%
“…The starting ceramics were synthesized by sintering route (1040 o C, 4 h duration) using reagent grade Cu carbonate hydroxide, and Ni, Co, Mn carbonate hydroxide hydrates [12][13][14]. The paste was prepared by mixing powder of basic Cu 0.1 Ni 0.1 Co 1.6 Mn 1.2 O 4 ceramics with МБ-60 glass, Bi 2 O 3 (used as inorganic binder) and some organic vehicle.…”
Section: Nanoinhomogeneous Ceramics Preparationmentioning
confidence: 99%
“…[7]. The structures obtained could be used as a basis for the preparation of multifunctional materials, where the voids between the columns could be filled with some other functional material, i.e.…”
Section: Magnetic Properties Of Barium Ferrite Powder and Depositsmentioning
confidence: 99%
“…Several techniques have been used to prepare such films, e.g. thermal spraying [7], electrophoretic deposition [8] and screen printing [9][10][11]. Recently, it was reported that materials with artificial structures show very interesting properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…The above facts indicate that relatively easy diffusion of cations through the whole film occurs during the infiltration and melt-texturation process. Since the 2 1 1 phase was present in over-stoichiometric amount, it was not completely consumed in reaction (3). It can be assumed that the Y 2 BaCuO 5 grains, which are probably precipitated in process of solidification are very fine.…”
Section: Preparation Of Ybco Melt-textured Thick Filmsmentioning
confidence: 99%
“…for high power microwave resonators, superconducting fault limiters, magnetic shields, filters and antennas [1][2][3][4]. The thick film technologies allow the low cost production of large area coatings of complex shape with relative ease.…”
Section: Introductionmentioning
confidence: 99%